Teaching Clinical Reasoning to Medical Students: A Case-Based Illness Script Worksheet Approach - Michael Levin; David Cennimo; Sophia Chen; Sangeeta Lamba (Association of American Medical Colleges, 2016)
Abstract Introduction Clinical reasoning is a fundamental part of a physician's daily workflow. Yet it remains a challenging skill to develop formally, especially in preclerkship-level early learners. Traditionally, medical students learn clinical reasoning informally through experiential opportunities during their clerkship years. This occurs in contrast to the more structured, explicit learning of the basic sciences and physical diagnosis during the preclerkship years. To address this need, we present a flipped classroom case-based approach for developing clinical reasoning skills based on problem representation and the use of a structured illness script worksheet as a model. Methods Students were given a short introduction via screencast to introduce clinical reasoning and related terminology such as problem representation and semantic qualifiers. They also received a case vignette and an illness script worksheet to prepare them for in-class discussion. Students used this worksheet to practice clinical reasoning in a small-group session that was held in our last organ system-based second-year course, prior to the start of the clerkships. Results In comparison to the traditional facilitator-led small-group sessions, where students would sequentially answer a set of defined content-based questions to explore a clinical case, 80% of students preferred the new framework that incorporates problem representation and the illness script worksheets. Faculty facilitators found the structure of the illness script worksheet helpful in leading a clinical reasoning small-group session. Discussion Based on the results of this pilot, we plan to systematically implement this clinical reasoning framework in our preclerkship curriculum.